2011
DOI: 10.1111/j.1469-8749.2011.03912.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome and adverse effects of selective dorsal rhizotomy in children with cerebral palsy: a systematic review

Abstract: There is lack of evidence concerning the long-term outcomes after SDR. Future studies need to clarify the long-term influence of SDR - especially in the ICF domains of activity and participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 39 publications
0
57
0
1
Order By: Relevance
“…Judicious intraoperative EMG monitoring is a widely performed and evidence-based approach and used to mitigate against severe lower limb weakness and incontinence (36). The literature suggests that in the long term, patients may experience increased lordosis and hip subluxation (6,32,37,38), but there is insufficient evidence to attribute the complications to SDR or the natural history of CP (30). However, the single-level laminectomy aims to significantly reduce the likelihood and severity of these complications (11).…”
Section: Outcome Of Sdrmentioning
confidence: 99%
“…Judicious intraoperative EMG monitoring is a widely performed and evidence-based approach and used to mitigate against severe lower limb weakness and incontinence (36). The literature suggests that in the long term, patients may experience increased lordosis and hip subluxation (6,32,37,38), but there is insufficient evidence to attribute the complications to SDR or the natural history of CP (30). However, the single-level laminectomy aims to significantly reduce the likelihood and severity of these complications (11).…”
Section: Outcome Of Sdrmentioning
confidence: 99%
“…In their review of long-term adverse effects of SDR, Grunt et al 25 reported that back pain and spinal abnormalities were common, including kyphosis, scoliosis, lumbar lordosis, spondylosis and spondylolisthesis. But they found insufficient evidence to conclude such abnormalities are the direct result of SDR rather than related to the natural history of spastic CP.…”
Section: Outcomes Of Selective Dorsal Rhizotomymentioning
confidence: 99%
“…Intrathecal baclofen pump insertion,16 selective dorsal rhizotomy17 and deep brain stimulation18 are all available at highly specialist centres in the UK. Detailed assessment and patient selection is essential and there needs to be clear communication between the specialist centre and all other multidisciplinary teams involved with the child and family to ensure close monitoring and follow-up is maintained (see table 4).…”
Section: Clinical Carementioning
confidence: 99%